Exploration of Ethnomathematics in Saung Ranggon of Cikedokan Village Cikarang Barat Through Learning Geometry - Niken Fijayanti; Wahidin Wahidin (Journal of Mathematics and Mathematics Education, 2024)
The aims of this study were (1) to know the concept of geometry with geometric material, (2) to know the concept of geometry with geometric material, (3) to know the concept of geometry with geometric transformation material, and (4) to know the development of numeration contained in the design. Saung Ranggon traditional house. This research is a qualitative research with an ethnographic approach. Data collection techniques in this study used interviews, observation, and documentation techniques, as well as data analysis using triangulation techniques with the Spradley model consisting of domain analysis, taxonomic analysis, and component analysis. The results of this study are the geometric concepts contained in the design of the Saung Ranggon traditional house, namely: the concept of a flat shape (rectangle that can be seen from the door, a square that can be seen from the side wall, a triangle that can be seen from the ventilation section, a trapezoid that can be seen from the back wall, rhombus which can be seen from the fence section, and circles which can be seen from the old well), the concept of geometric shapes (tubes), the concept of transformation geometry (reflection on the  axis,  axis,  axis), and numeration development is used to solve the cost problem.